PENGARUH PENGETAHUAN DAN SIKAP IBU TERHADAP PENGGUNAAN METODE KONTRASEPSI JANGKA PANJANG (MKJP) DI KP.KENDAL TAHUN 2022 - Rizki Ayu Mardika; Bela Novita Amaris Susanto; Ayu Pratiwi (Nusantara Hasana Journal, 2023)
Long Term Contraception Method is a form of contraception that is very effective for prevention, avoiding birth spacing and not affecting sexual intercourse which can last from 3 years to a lifetime. The effect of the Family Planning Program task in this case is clear, namely reducing the total fertility rate. This research method uses cross sectional, accidental sampling technique with a total of 60 respondents. The statistical test used was the Chi-Square test. Objective: To determine the effect of knowledge and attitudes of mothers on users of long-term contraceptive methods. The results showed that mother's knowledge variable with MKJP P-Value was 0.028 <0.05. And the mother's attitude variable with MKJP P-Value 0.030 <0.05. So that there is an influence between mother's knowledge with MKJP and mother's attitude with MKJP. There is an influence between mother's knowledge and mother's attitude towards the use of MKJP.